Race, work, and leadership : new perspectives on the black experience - Roberts, Laura Morgan,; Mayo, Anthony J.,; Thomas, David A., 1956- (Harvard Business Review Press, 2019)
Race, Work, and Leadership is a rare and important compilation of essays that examines how race matters in people's experience of work and leadership. What does it mean to be black in corporate America today? How are racial dynamics in organizations changing in a post-Obama era? How do we build inclusive organizations? Inspired by and developed in conjunction with the research and programming for Harvard Business School's 2018 celebration of the 50th anniversary of the founding of the HBS African American Student Union, this groundbreaking book shines new light on these and other timely questions and illuminates the present-day dynamics of race in the workplace. Contributions from top scholars, researchers, and practitioners in leadership, organizational behavior, psychology, sociology, and education test the relevance of long-held assumptions and reconsider the research approaches and interventions needed to understand and advance African Americans in work settings and leadership roles. At a time when there are fewer African American men and women in corporate leadership roles (following a peak in 2002), Race, Work, and Leadership will stimulate new scholarship and dialogue on the organizational and leadership challenges of African Americans and become the indispensable reference for anyone committed to understanding, studying, and acting on the challenges facing leaders who are building inclusive organizations.--